Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Pegawai Bappeda - Angel Pricilia, Laras; Effiyaldi; Paul Karolus Pasaribu, Johni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to analyze the effect of leadership style and work discipline on employee performance at Bappeda Jambi City. This study uses quantitative methods and data collection techniques using questionnaires. The sample used was all Bappeda employees totaling 70 employees, using saturated sampling as a sampling technique. The research data were analyzed using linear regression analysis techniques using SPSS version 26. The results showed that the variables of leadership style and work discipline partially and simultaneously had a positive and significant effect on the performance of Jambi City Bappeda employees. This means that 40% of the dependent variable (employee performance) can be explained by the independent variables, namely leadership style and work discipline simultaneously. Meanwhile, the remaining 0.600 or 60% is influenced by other variables outside this research model.